Haglund's syndrome: Radiographical evaluation and its clinical relevance - Aradhana Sanga; Rajesh K Kushwaha; Rakesh K Vidrohi; Prerna Sanga; Saikat Kumar Dey (Wolters Kluwer Medknow Publications, 2023)
Background: Haglund's syndrome an important cause of posterior heel pain presents with a prominent bony contour, a retrocalcaneal bursitis or achillis tendinitis these can also occur in isolation hence for the diagnosis of etiology of Haglund's disease certain radiological parameters and soft tissue parameters have been created to evaluate the anatomical variations which will assist in its exact diagnosis. Study aims to distinguish between the bony and soft tissue causes of Haglund's disease radiologically. Methodology: After Institutional ethical committee clearance an observational cross-sectional study was conducted with subjects coming to radiology OPD for X-ray foot with complains of posterior heel pain fulfilling inclusion and exclusion criteria were examined for X-ray lateral view of foot. Parameters like calcaneal inclination angle (CIA), Fowler Philip angle (FPA), parallel pitch line (PPL), Steffenson & Evenson angle (SEA) measured, posterior/calcaneal spur and posterior calcaneal step were noted. The data obtained was analyzed for mean, Standard deviation, sensitivity % and false negative %. Result: Sensitivity of the parameters were analyzed to find CIA, SEA &PPL to be 63.3%, 55% and 55% sensitive respectively. CIA could be assigned most sensitive but regarding soft tissue parameters none were sensitive. Conclusion: CIA, SEA & PPL were found to be sensitive among bony parameters. But none of the soft tissue parameters were sensitive radiologically highlighting a need for its correlation with clinical symptom in peripheral health centers where MRI is not available. Sensitivity of bony and soft tissue parameters were analyzed to find CIA, SEA & PPL to be sensitive. CIA could be assigned most sensitive among bony parameter but with regards to soft tissue parameters none were sensitive.